2014
DOI: 10.1021/ar5000133
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assemblies Based on the “Outer-Surface Interactions” of Cucurbit[n]urils: New Opportunities for Supramolecular Architectures and Materials

Abstract: Supramolecular architectures and materials have attracted immense attention during the last decades because they not only open the possibility of obtaining a large variety of aesthetically interesting structures but also have applications in gas storage, sensors, separation, catalysis, and so on. On the other hand, cucurbit[n]urils (Q[n]s), a relatively new class of macrocyclic hosts with a rigid hydrophobic cavity and two identical carbonyl fringed portals, have attracted much attention in supramolecular chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
318
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 369 publications
(333 citation statements)
references
References 43 publications
8
318
0
Order By: Relevance
“…38 It can therefore be anticipated that the modification of CB [6], either by chemical or physical means, provides an alternate option for the enhancement of the adsorption ability. 39,40 The high quadrupolar moment of CO 2 can be efficiently used for sequestration by logically employing a polar functional group with a high affinity towards CO 2 for modifying the pores of CB [6]. Such modifications will enhance the adsorption capacity as well as the selectivity for CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…38 It can therefore be anticipated that the modification of CB [6], either by chemical or physical means, provides an alternate option for the enhancement of the adsorption ability. 39,40 The high quadrupolar moment of CO 2 can be efficiently used for sequestration by logically employing a polar functional group with a high affinity towards CO 2 for modifying the pores of CB [6]. Such modifications will enhance the adsorption capacity as well as the selectivity for CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…101 In this way, CBs have been explored in a multitude of applications, ranging from drug delivery, molecular recognition, and self-assembly and have also been explored as multivalent scaffold. [102][103][104] Recent studies propose that the electrostatic positive outer surface of CB[n]s provides a balance in the various supramolecular driving forces for CB[n] assembly, including other CB[n]s, aromatic moieties, inorganic molecules based on hydrogen bonding between methine or methylene groups on the outer surface of CB[n]s. 101 Due to the larger cavity volume, CB [8] is able to host two guests in its cavity to form a 1:1:1 ternary complex affording high selectivity and molecular recognition. The guest pairs are composed of an electron-deficient guest, that is, viologen derivatives, and an electron-rich guest, that is, naphtol.…”
Section: Host-guest Complexes Based On Cucurbit[n]urilmentioning
confidence: 99%
“…[5,6] More recent works confirmed that the presence of polychloridometallate ions, in particular [M d-block Cl x ] nanions (M d-block = Cd, Zn, Cu, Co, Ni, and so on), which are structure inducers, could lead to the formation of novel Q[n]-based polydimensional coordination polymers. [2,7] For example, the formation of coordination complexes of lanthanide cations and cucurbit [7]uril (Ln 3+ /Q [7]) is generally very difficult, whereas one-dimensional coordination polymers easily form in the presence of [M d-block n-anions. [2,7,8] Driving forces, which are defined as the outer-surface interaction of cucurbit[n]uril, are the unusual hydrogen bonding of the "waist region" methine (ϵCH) or bridge methylene (=CH 2 ) groups on the back of Q[n] molecules with oxygen and chloride from the polychloridometallates.…”
Section: Introductionmentioning
confidence: 99%
“…[2,7] For example, the formation of coordination complexes of lanthanide cations and cucurbit [7]uril (Ln 3+ /Q [7]) is generally very difficult, whereas one-dimensional coordination polymers easily form in the presence of [M d-block n-anions. [2,7,8] Driving forces, which are defined as the outer-surface interaction of cucurbit[n]uril, are the unusual hydrogen bonding of the "waist region" methine (ϵCH) or bridge methylene (=CH 2 ) groups on the back of Q[n] molecules with oxygen and chloride from the polychloridometallates. These forces also include interactions of electron-deficient carbonyl carbon sites of Q[n] molecules with chloride of polychloridometallates and with portal carbonyl oxygen atoms of adjacent Q[n] molecules (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation